SARS-CoV-2 Causes Mitochondrial Dysfunction and Mitophagy Impairment - Shang, Chao; Liu, Zirui; Zhu, Yilong; Lu, Jing; Ge, Chenchen; Zhang, Cuiling; Li, Nan; Jin, Ningyi; Li, Yiquan; Tian, Mingyao; Li, Xiao (Frontiers in Microbiology, 2022)
Mitochondria, which is essential for adequate innate immune response, energy metabolism and mitochondria reactive oxygen species (ROS) production, might be in the cross fire of Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and host cell defense. However, little is known about interactions between mitochondria and SARS-CoV-2. We performed fluorescent microscopy and found an enrichment of SARS-CoV-2 replication products double stranded RNA (dsRNA) within mitochondria. The entry process of dsRNA might be mediated by Tom20 as observed by reduced mitochondrial localization of SARS-CoV-2 dsRNA in Tom20 knockdown cells. Importantly, decreased mitochondrial localization of dsRNA, as well as mitochondrial membrane stabilizers mdivi-1 and cyclosporin A, inhibited viral load in cells. Next, we detected mitochondrial dysfunction caused by SARS-CoV-2 infection, including mitochondrial membrane depolarization, mitochondrial permeability transition pore opening and increased ROS release. In response to mitochondrial damage, we observed an increase in expression and mitochondrial accumulation of Pink1 and Parkin proteins, as well as Pink-1-mediated recruitment of P62 to mitochondria, suggesting initiated mitophagy for mitochondrial quality control and virus clearance. Nevertheless, we observed that mitophagy was inhibited and stayed in early stage with an unchanged Hsp60 expression post SARS-CoV-2 infection. This might be one of the anti-autophagy strategies of SARS-CoV-2 and we used co-immunoprecipitation to found that SARS-CoV-2 infection inhibited P62 and LC3 binding which plays a critical role in selective envelopment of substrates into autophagosomes. Our results suggest that mitochondria are closely involved in SARS-CoV-2 replication and mitochondrial homeostasis is disrupted by SARS-CoV-2 in the virus-cell confrontation.